(untitled) (International Journal of Engineering and Computer Science, 2017)
Now days, every single human being is addicted by technology. Technology becomes one of the basic needs. So, we have also responsible for the data which is transmitting over the network. We have to maintain the records, security & oppose the hacking that data from the third persons. Therefore our group focus on these issues & try to implement such kind of system which is comprises in the class of ‘data security’ which named as “Twice Precaution during Transmission of hidden data”. There are two phases included in our system. 1st phase is depends upon image & data encryption. 2nd phase is depends upon recovery of that image & data. After encrypting image & data, the encrypted data is embedded into the encrypted image. At the end of 1st phase, we get image encryption key & after embedding the data into image, we get data hiding key. Both keys, encrypted form of image & data is transmitted to receiver at another end side. Both keys are essential to decrypt image & data successfully. After decryption we get the original image as well as data.